2017
DOI: 10.4103/jde.jde_36_16
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Enteritis: An Uncommon Manifestation of Systemic Lupus Erythematosus as an Initial Presentation

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disorder generally affects young to middle-aged women, commonly presenting as a triad of fever, rash, and joint pain but can affect multiple organs and can present in a complex fashion, varying based on the degree and severity of organ involvement. The differential for abdominal pain and diarrhea in SLE is vast and can include VIPomas, serositis, pancreatitis, intestinal vasculitis, and protein – losing enteropathy, gluten – enteropathy, intestinal pseudo-obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Along with other systems, it can affect the gastrointestinal tract (GIT). [ 1 ] GIT-related symptoms occur in up to 40%–50% of SLE patients and involve any organ along with the GIT. About 75% of patients with GI-SLE have pain abdomen as the most common symptom.…”
Section: Discussionmentioning
confidence: 99%
“…Along with other systems, it can affect the gastrointestinal tract (GIT). [ 1 ] GIT-related symptoms occur in up to 40%–50% of SLE patients and involve any organ along with the GIT. About 75% of patients with GI-SLE have pain abdomen as the most common symptom.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopy is usually not helpful nor necessary in making the diagnosis of lupus enteritis since only superficial tissue is analyzed[19,20]. The yield of biopsy is only about 6%[17]. Endoscopy with biopsy should be reserved to confirm or rule out alternative etiologies in cases of diagnostic uncertainty[13].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed prevalence of other GI diagnoses related to SLE, namely intestinal pseudo-obstruction (2%), followed with protein-losing gastroenteropathy (1.9%), and acute pancreatitis (0.7-4%). 8,9 Other rare causes include celiac disease and inflammatory bowel disease (IBD). 8 Lupus enteritis was defined by the British Isles Lupus Assessment Group (BILAG) as vasculitis or inflammation of the small bowel with supportive image and/or biopsy findings.…”
Section: Introductionmentioning
confidence: 99%
“…8 Lupus enteritis was defined by the British Isles Lupus Assessment Group (BILAG) as vasculitis or inflammation of the small bowel with supportive image and/or biopsy findings. 9 The most common presenting symptom of lupus enteritis is abdominal pain (97%), followed by vomiting (42%), diarrhea (32%), and fever (20%). 10 There are no specific markers for lupus enteritis which can aid in diagnosis, but a recent study conducted by Aso et al has shown that anti-ganglionic nicotinic acetylcholine α3 subunit (anti-gAChRα3) could be a potential biomarker for lupus enteritis.…”
Section: Introductionmentioning
confidence: 99%